Indonesian national qualification framework & MBKM curriculum of PAI doctoral in UIN Sunan Kalijaga - Hayani, Aida; Sutrisno, Sutrisno; Sukiman, Sukiman (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
The curriculum is so important in Higher university. The existence of compulsory higher education and transformed into an independent agency without interest and political elements stored in it. This Study aims to describe the Indonesian National Qualification Framework and MBKM Curriculum of PAI Doctoral in PTKI. This research's findings are as follows the reality is that the recruitment pattern of educational institutions cannot be separated from the grip of politics. For example, many top leaders in higher education are still wrong the mention KKNI, the error lies in how to understand the concept of KKNI only to the extent of the curriculum. With the implementation of the curriculum, it is hoped that PTKI will meet the needs of employment opportunities and can play an important and active role in social life at the national and international levels. In addition, all PTKI graduates can obtain equality in terms of rights and recognition related to further education in all countries that have the same qualifications that have been determined by all graduate users